A Systematic Review of the Use of Social Media for Recruitment of Participants in Nutrition, Obesity, and Physical Activity Related Studies. (7th June 2021) - Ellington, Malik; Connelly, Jeneene; Clayton, Priscilla; Collazo-Velazquez, Christina; Lorenzo, Yaisli; Trak-Fellermeier, María Angélica; Palacios, Cristina
Abstract: Objectives: To analyze the effectiveness of social media for recruitment compared to traditional methods, to calculate an average impression/reach to participant recruitment ratio from social media, and to identify the social media platforms most effective in recruiting study participants. Methods: Studies within any date of publication were identified from 5 databases and included if any social media platform was used for the recruitment of participants of all age groups and if studies were linked to nutrition, obesity and physical activity. Studies without results on number of participants recruited using social media or those targeting participants with chronic conditions were excluded. Results: 173 total studies were identified, 54 were duplicates, 61 were removed after initial screening and another 34 were removed after full text review; resulting in 24 studies included in this review. Among studies using both traditional (printed, word of mouth, etc) and social media methods for recruitment, average recruitment was 54% from traditional methods compared to 40% from social media. A total of 14 studies reported data on recruitment cost with an average of 33 per participant (range 0–258). Average participants recruited via social media to an "in-person" interventional study was 128 (range 8–426), to participate in an online survey 2, 739 (range 63–17, 069), and for other online delivered interventions 349 (range 3–1242). Regarding advertisement (ad) reach and interaction, 18 studies that reported results showed that 0.73% of those reached by study ads were enrolled and 30.7% of those that interacted with ads were enrolled. The most frequent social media platform used for recruitment was Facebook (97%), followed by Twitter (17%), and Instagram (4%). Conclusions: Among studies using both traditional methods and social media, there were less people recruited using social media. While social media was able to reach more potential participants, only one third of those who interacted with ads were enrolled. Many of the studies only required participants to respond to a survey; therefore, more research is needed to identify the effectiveness of using social media for recruiting participants for studies that require a more intense participation. Funding Sources: National Institutes of Health – Eunice Kennedy Shriver National Institute of Child Health and Human Development.